Detection and localization of potholes in roadways using smartphones (2016)
A system for the detection and localization of roadway potholes is proposed and is aimed at collecting data on the roadway potholes using the accelerometer, GPS and compass that are embedded into smartphones using the Android operating system. This system has a scalable mobile architecture that contributes to capturing environment information using multiple devices with a large geographic coverage.